Leap Kepler Banhatti Indices of Some Chemical Drugs - V. R. Kulli (International Journal of Mathematics And its Applications, 2025)
In this paper, we introduce the leap Kepler Banhatti and modified leap Kepler Banhatti indices and their corresponding exponentials of a graph. Furthermore, we compute these newly defined leap Kepler Banhatti indices and their corresponding exponentials for certain important molecular structures such as chloroquine, hydroxychloroquine and remdesivir.